Documental sobre la revitalización de la identidad sociocultural de la comunidad montuvia del cantón Santa Ana - Palma Sánchez, Francisco Xavier (2015)
The Ethnographic Documentary: “Abanderados Rebeldes”, recorded in the department of Santa Ana in the province of Manabí Ecuador, with the objective of collecting social, cultural and historic data of the Montuvian Community. The documentary establish the debate and dialogue about the identity and socio cultural origin through a cultural and communicative propose, contributing in this way to the revitalization of the Province of Manabí in Ecuador. Inquire about the ancestral, cultural and politic values and the social protagonist of the Montuvian Culture, were the process made by the author to explain the topic with academic and social depth. The investigation work is oriented to three key and academic points that look for the revitalization of the ancestral groups in the province of Manabí and in Ecuador too. The Communication, History and Culture, essential elements for the reconstruction of the identity and self cultural definition in the social area. With this words, a theoretic exposition will be given about topic of communication and culture, the Montuvian culture, the ethnographic cinema, and the documentaries as re constructor of the cultural memory, additionally several schemes, recording dates, story line and screenplays that join directly a communicative and cultural product. This investigative work was built based on the micro tales obtained from the ethnographic interviews done to people of the third age and young people of the communities from Santa Ana, with an additional of the academic opinions of several university teachers, historians and experts in the topic of the Montuvian culture of Manabí.